Effects of Autochthonous Yeast Cultures on Some Quality Characteristics of Traditional Turkish Fermented Sausage Sucuk - Ozturk, Ismet; Sagdic, Osman; Yetim, Hasan (KOREAN SOC FOOD SCIENCE ANIMAL RESOURCES, 2021)
The objective of this study was to determine the effects of yeast cultures (Candida zeylanoides and Debaryomyces hansenii) isolated from traditionally dry fermented Turkish sucuks, on some physicochemical and microbiological properties of the product. Eight different batches of the sucuks were produced by the inoculation of yeast and lactic acid bacteria (LAB) cultures (Lactobacillus curvatus, Lactobacillus plantarum and Lactobacillus sakei) in different combinations. The sucuks were ripened for 12 days and analyzed at 1st, 6th, and 12th days of ripening. Percent moisture content, pH, water activity (a(w)) and residual nitrite values of the sucuk inoculated with the yeast cultures were higher at the end of the ripening. The use of yeast cultures decreased hardness, gumminess, and chewiness values of the sucuk while increased adhesiveness values. Major volatile groups were aldehydes, terpenes, and sulphur compounds in the sucuk samples. The most noticeable results were for sensory properties of the sucuk that were positively improved by the yeast cultures.
Keywords: Turkish fermented sucuk; indigenous yeast; texture; volatile; DEBARYOMYCES-HANSENII; STARTER CULTURES; VOLATILE COMPOUNDS; SENSORY QUALITY; SALT REDUCTION; NITRITE; GENERATION; DYNAMICS; STRAINS; SPP.; Food Science & Technology